Kajian Literatur Tentang Strategi Pemasaran Susu : Tantangan dan Peluang - Maskur, Camal Adi; Ervandi, Mohamad (Universitas Muhammadiyah Gorontalo, 2025)
The dairy industry is an important sector in the global economy, which faces various challenges and opportunities in its marketing strategy. This research aims to review the literature related to dairy marketing strategies, highlighting trends, innovations and challenges faced by industry players. Based on the results of the literature review and research, it shows that factors such as changing consumer preferences, technological innovation, and sustainability play an important role in determining the success of dairy marketing strategies. The article also discusses various marketing approaches, including digital marketing, branding, and product diversification, as well as challenges such as intense competition, regulation, and fluctuating raw material prices. Industri susu merupakan salah satu sektor penting dalam perekonomian global, yang menghadapi berbagai tantangan dan peluang dalam strategi pemasarannya. Penelitian ini bertujuan untuk mengulas literatur terkait strategi pemasaran susu, dengan menyoroti tren, inovasi, serta tantangan yang dihadapi oleh pelaku industri. Berdasarkan hasil kajian literatur dan penelitian menunjukkan bahwa faktor seperti perubahan preferensi konsumen, inovasi teknologi, dan keberlanjutan memainkan peran penting dalam menentukan keberhasilan strategi pemasaran susu. Artikel ini juga membahas berbagai pendekatan pemasaran, termasuk pemasaran digital, branding, dan diversifikasi produk, serta tantangan seperti persaingan yang ketat, regulasi, dan fluktuasi harga bahan baku.